Determinan Electronic Loyalty (e-Loyalty) Pada Website - Prapti Antarwiyati; Agus Lukman Nurhakim; Hadri Kusuma (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2010)
The purpose of this research was to investigate the factors influencing consumer’s loyalty toward e-commerce website. The samples were those who used and interacted to the website. We applied accidental sampling and the questionnaires were distributed manually and through on line. Returned and processed questionnaires were from 175 respondents. Ten of 14 hypotheses in our research were supported by the data. Those hypotheses are the relationship among the factors of perceived ease of use, perceived usefulness, trust, social presence, enjoyment and value, patronage intent and e- loyalty towards the website. Keywords: perceived ease of use, trust, social presence, enjoyment and value, consumer’s loyalty toward e-commerce website